Pengaruh Iklim Organisasi dan Disiplin Kerja Terhadap Efektivitas Kerja pada Kantor Dinas Pertanian Kabupaten Agam Selama Masa Covid-19 - Anisa, Febri; Yanti, Novi (Ekasakti Matua Jurnal Manajemen, 2024)
This study aims to examine and analyze 1). the influence of organizational climate on the work effectiveness of employees at the Agam Regency Agricultural Service Office during the Covid-19 Period 2). the effect of work discipline on the effectiveness of work employees at the Agam Regency Agricultural Service Office during the Covid-19 period, 3). the influence of organizational climate and work discipline simultaneously on the effectiveness of employees' work at the Agam Regency Agricultural Service Office during the Covid-19 Period. Population 80 people and sample 80 people. The data analysis method is Multiple Linear Regression Analysis and determinant coefficients while the hypothesis testing method is the t-test and F-test. The results of the study show 1. Partially, organizational climate variables have a positive and significant effect on the work effectiveness of employees at the Agam Regency Agriculture Office during the Covid period. -19, 2. Partially, the work discipline variable has a positive and significant effect on the work effectiveness of employees at the Agam Regency Agricultural Service Office during the Covid-19 Period 3. The organizational climate and work discipline variables simultaneously or simultaneously have a significant and significant effect on the employee's work effectiveness at the Agam Regency Agriculture Service Office during the Covid-19 Period, 4. The contribution of the influence of organizational climate and work discipline on the work effectiveness of employees at Agam Regency Agricultural Service Office during the Covid-19 period was 42.50% while the remaining 57.50% was influenced by others examples competence, compensation and others.